Impact of source/drain and bulk engineering on LFN performance of n- and p-MOSFET. (September 2017) - Ioannidis, E.G.; Rohracher, K.; Roger, F.; Pflanzl, W.C.; Leisenberger, F.P.; Wachmann, E.; Seebacher, E.; Vescoli, V.
Abstract: In this paper, we present a detailed investigation of the impact of different Lightly Doped Drain (LDD) implants and different well doping on the low frequency noise performance of n- and p-MOS devices from a CMOS technology node. We investigate the impact of three different devices. Two with the same LDD implant but different well doping and one with different LDD implant cocktail. The results demonstrate that the different bulk doping does not affect the low frequency noise performance of the devices. On the other hand there is a serious impact on the noise level of the device with the different LDD implant. In order to further support our results we investigated devices with different lengths in the linear and saturation region of operation.